(untitled) (Herald of Journalism, 2016)
Author of the XIX century Muhammad Salih Babadjanov discloses topical issues of Kazakh society of his time. Such as the problem of the place of residence of the local population, the problem of education of young people (in particular the definition of writing), the problem of determining the place in society, health and health care problem, the problem of the relationship and interaction of the Kazakh people with other people, the problem is a simple legal illiteracy of the population and the problem of breeding and conservation of horses for racing.